Seed Germination Enhancement of Ziziphus spina-christi (L.) Willd. and Ziziphus mucronata Willd. (Rhamnaceae) Using Different Pre-sowing Treatments in Ethiopia - Seid, Mohammed Adefa; Wondimu, Tigist; Degu, Asfaw; Assefa, Awol (Annals of Arid Zone, 2024)
The stony endocarp and impermeable seed coat of Ziziphus, including fleshy mesocarp inhibit seed germination in both genera. In present study effects of different pre-sowing treatments on seed germination of Z. spina-christi and Z. mucronata was studied. Seeds of each species were collected from the Central and Southern Rift Valley and Northeast Ethiopia. Seeds of each Ziziphus species, after being divided into cracked and uncracked seed-stone groups were subjected to eight different pre-sowing treatments and planted in pots. The mean germination percentage (GP), mean daily germination (GD), mean germination time (GT), and mean germination index (GI), as well as two-way ANOVA and Tukey’s Honestly Significant Difference (THSD), were computed. The two-way ANOVA showed that there exists a significant mean difference among treatment groups under all germination parameters at p